We are Big Data The Future of the Information Society - Klous, Sander; Wielaard, Nart.; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2016)
Sander Klous holds a PhD in High Energy Physics and contributed to the discovery of the Higgs boson at CERN (Nobel prize 2013). Klous works at KPMG and is professor in Big Data at the University of Amsterdam. Nart Wielaard is a self-employed consultant and business writer. He develops compelling and clear stories on complex topics for a broad range of clients. Wielaard specializes in the domain where technology, society and business meet. .
1.Big, bigger, biggest data -- 2.Remove fear and conquer resistance -- 3.You ain't seen nothing yet -- 4.Hitting the bullseye first time around -- 5.Data stimuli for a better world -- 6.Data analytics is the society -- 7.Wanted: thousands of Sherlock Holmes clones -- 8.The question is more important than the answer -- 9.Transparency, a weapon for citizens -- 10.Systems determine our behavior -- 11.A new ecosystem. .
Keywords: Engineering; Computers and civilization; Technological innovations; Economic sociology; Technology and Engineering; Computers and Society; Innovation and Technology Management; Economic Sociology